Simplified wide-range ultrasonic measurements using the sensor three-dimensional system - Seiichi Morokuma (Journal of Medical Ultrasound, 2018)
We developed a simplified three-dimensional ultrasonic device that can scan a wide area and performed measurements in the scanned area. The system is more compact than magnetic resonance imaging (MRI) systems and can measure random cross sections by acquiring volume data over a wide range through freehand scanning with a magnetic sensor unit that detects the transducer position. The system was applied successfully to a case with a huge myoma. Our system, in ways similar to computed tomography or MRI systems, can support both the objective understanding of the pathology of huge tumors and follow-up determinations of tumor diameters at arbitrary cross sections in the volume data.